The Development of Investment Banking Industry and the Application of Supply Chain Finance in Commercial Bank Credit Business - Wang Bozhen (SHS Web of Conferences)
Under economic globalization, the investment banking industry has experienced rapid development driven by cross-border capital flows, mergers and acquisitions, and financial innovation, while supply chain finance (SCF) has emerged as a transformative tool in commercial bank credit services. This paper examines the dual dynamics of investment banking expansion and SCF adoption, focusing on China’s banking sector, with China Merchants Bank (CMB) as a case study. The study highlights that globalization has propelled investment banks toward internationalization, diversification, and technological integration, enabling them to support global capital markets and corporate restructuring. Simultaneously, SCF addresses financing challenges for SMEs by leveraging transactional data and core enterprise creditworthiness, enhancing credit efficiency and risk management. CMB exemplifies these trends through its global investment banking footprint and innovative SCF platforms like “Cloud Chain,” which integrates fintech solutions such as blockchain and AI. Findings suggest that commercial banks must prioritize technological adoption, regulatory compliance, and strategic partnerships to thrive in globalized financial ecosystems. This paper contributes insights into the evolving roles of investment banking and SCF in fostering financial inclusivity and resilience amid globalization, offering practical implications for banks navigating interconnected markets.